Assessment of the Tilapia industry in Nigeria for economic trait prioritization - Cole, Steven (Abacusbio, 2023)
This report seeks to understand the value of genetic improvement for different traits for Tilapia in Nigeria (in economic and non-market preference terms), with the ultimate goal of developing a breeding objective based on underlying economic models (and/ or non-market preferences). This would provide valuable information for the advancement of selection candidates with performance tailored to meet the needs of different groups of Tilapia farmers in Nigeria, including men and women farmers, and broader supply chain participants.